Perancangan Sistem Inventory Pada Toko Andre Ikan Hias - Baresi Bahtiar; Dwi Noor Saputra; Muhamad Febriyanto; Thoyyibah T (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Stores engaged in the field of agricultural materials in the sale of ornamental fish. Ornamental fish is a fishery commodity that is cultivated continuously. If fishing is carried out continuously, the balance of the ecosystem will be disrupted. Therefore, there are several commodities scattered in several areas to cultivate this ornamental fish so that it does not become extinct. Build an application-based inventory information system that provides easy data management for the admin. Designing an inventory system to present information quickly and precisely. As one of the requirements for the Practical Work course in the Undergraduate (1) program for the Informatics Engineering study program at Pamulang University (UNPAM). Observation method, namely data collection that is carried out directly from observation and recording in the field. Library Method, namely data collection is done by means of data taken or collected from books related to the implementation of Job Training. Interview method, namely data collection is done by asking directly to the source. System Development, namely the preparation of a new system to replace or improve the existing system. This chapter describes several proposals or changes to the running system, and software and hardware specifications that are used as media for implementing the system to be implemented, as well as software test results by analyzing the efficiency and effectiveness of the system made compared to the running system.